Paternal age and telomere length in twins: the germ stem cell selection paradigm - Hjelmborg, Jacob B (Aging Cell, 2015)
Telomere length, a highly heritable trait, is longer in offspring of older fathers. This perplexing feature has been attributed to the longer telomeres in sperm of older men and it might be an ‘epigenetic’ mechanism through which paternal age plays a role in telomere length regulation in humans. Based on two independent (discovery and replication) twin studies, comprising 889 twin pairs, we show an increase in the resemblance of leukocyte telomere length between dizygotic twins of older fathers, which is not seen in monozygotic twins. This phenomenon might result from a paternal age-dependent germ stem cell selection process, whereby the selected stem cells have longer telomeres, are more homogenous with respect to telomere length, and share resistance to aging.